2019
DOI: 10.5603/cj.a2018.0030
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma cathepsin S and trombospondin-1 in patients with acute ST-segment elevation myocardial infarction

Abstract: Background: The role of cathepsins in the pathological progression of atherosclerotic lesions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The levels of several cathepsins are elevated in cancer cells and tumor-associated cells, and increased secretion from tumors has been shown [5][6][7]. Also, cathepsins B, K, L and S are implicated in cardiovascular disease [8][9][10][11][12][13]. In addition, cathepsin B, L and S play important roles in the major histocompatibility complex (MHC) class II-mediated antigen processing and presentation [14][15][16].…”
Section: Cysteine Proteasesmentioning
confidence: 99%
“…The levels of several cathepsins are elevated in cancer cells and tumor-associated cells, and increased secretion from tumors has been shown [5][6][7]. Also, cathepsins B, K, L and S are implicated in cardiovascular disease [8][9][10][11][12][13]. In addition, cathepsin B, L and S play important roles in the major histocompatibility complex (MHC) class II-mediated antigen processing and presentation [14][15][16].…”
Section: Cysteine Proteasesmentioning
confidence: 99%
“…Activation of these signaling molecules is controlled by the transduction pathway (activated by binding of secreted factors to cell membrane receptors) and the mechanotransduction pathway (induced by changes in the rigidity of the extracellular matrix), which acts as an anchor for most cells, playing a key role in response to injury and stress) [17,19]. These molecules differ from structural proteins such as integrins, and bind transiently to specific receptors for intracellular signaling, including thrombospondin 1, to regulate tissue perfusion [20]. Largely, it can be said that the redox system also plays a role in repair of the extracellular matrix in diseases such as diabetes, either directly or via cell signaling [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that TSP-1 could have a protective role in preventing the expansion of healing myocardial infarcts [ 24 ], but another stated that low TSP-1 could be associated with major adverse cardiac events in ST-elevation myocardial infarction [ 25 ]. Befekadu et al [ 26 ] found TSP-1 rapidly declined after P CI even significantly lower than in healthy individuals. TSP-1 could probably be unrelated to infarct size of heart.…”
Section: Discussionmentioning
confidence: 99%